Relationship between sleep disorders and the efficacy of immune checkpoint inhibitors in older patients with non-small cell lung cancer - Liu, Zheng; Zhu, Hongjun; Wang, Kan (Frontiers in Oncology, 2026)
BackgroundImmune checkpoint inhibitors (ICIs) represent a critical treatment modality for older adults with advanced non-small cell lung cancer (NSCLC). The objective of this study was to investigate the potential relationship between sleep disorders, a condition commonly observed in this older population, and the efficacy of ICIs in treating advanced NSCLC.MethodsA total of 495 older patients with NSCLC who had distant metastases or local infiltration and were ineligible for surgical resection were consecutively enrolled in the study. All patients received either ICI monotherapy or combination therapy, and were followed up for 24 months. Sleep quality was assessed four times using the Pittsburgh Sleep Quality Index to assess the average severity of sleep disorders. Treatment conditions, clinical outcomes, and Grade 3–4 adverse events were documented, and associations were evaluated using multivariate logistic regression or Cox regression analysis.ResultsSleep disorders were associated with a reduced likelihood of achieving complete response/partial response/stable disease for ICI efficacy at 3 months (P = 0.002), an increased risk of gastrointestinal, liver, and lung toxicity over the 24-month follow-up (P = 0.014, P = 0.012, P = 0.036), and a decreased probability of survival at 24 months (P = 0.004). Sleep disorders were also associated with reduced progression-free survival and overall survival during the 24 months (P = 0.048, P = 0.002).ConclusionAmong older NSCLC patients receiving ICI treatment, sleep disorders are significantly associated with poorer treatment efficacy and a higher risk of multisystem adverse reactions. The findings of this study provide preliminary evidence for integrating sleep assessment into individualized ICI treatment strategies in this population.